2020
DOI: 10.3390/foods9080966
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Crossmodal Correspondence between Bubbles’ Size and Pouring Sounds’ Pitch in Carbonated Beverages

Abstract: Visual and auditory carbonation have been separately documented as being two sensory markers of perceived freshness in beverages. The aim of the present study is to investigate the cross-modal interactions between these two dimensions of carbonation. Three experiments focused on crossmodal correspondences between bubble size and pouring sound pitch, which have never been investigated with ecological stimuli. Experiment 1, using an implicit association test (IAT), showed a crossmodal correspondence between bubb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
2
6
0
2
Order By: Relevance
“…However, in the sound manipulation condition of Experiment 1, the refreshing expectation was enhanced with the unaltered (vs. low-pressure) sound. Moreover, in Experiment 2, the refreshing expectations were significantly enhanced when participants listened to the unaltered (vs. low-frequency) sound, which is in line with Roque et al’s study [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, in the sound manipulation condition of Experiment 1, the refreshing expectation was enhanced with the unaltered (vs. low-pressure) sound. Moreover, in Experiment 2, the refreshing expectations were significantly enhanced when participants listened to the unaltered (vs. low-frequency) sound, which is in line with Roque et al’s study [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Notably, the unaltered beer bottle pouring sound enhanced the refreshing expectations of NAB, and such effects were obtained regardless of the NAB image shown to participants (i.e., beer or can). On the one hand, as explained before, the obtained results are in line with previous research, where it has been shown that high-pitched sounds representing small bubbling (vs. low-pitched sounds/big bubbling) tend to be more congruent with fresher sparkling beverages [31]. On the other hand, this finding may also indicate that consumers can disentangle the image from the sound while shopping in e-commerce, thus not framing the multisensory experience of the image of a can, when accompanied by a beer bottle pouring sound, as semantically incongruent.…”
Section: Using Experiential Beer Sounds To Nudge Consumers Towards Nab Choices In Digital Shopping Environments (H2)supporting
confidence: 92%
See 2 more Smart Citations
“…Prior literature has demonstrated that sharp (vs. rounded) visual logos and sounds can provide reliable cues about the carbonation strength of a beverage (Ngo et al, 2012;Spence & Gallace, 2011). Even the pitch-size association and higher frequency sounds can influence the expectations of carbonation (e.g., smaller bubbles make higher frequency sounds, which leads to an expectation of a fresher beverage (Roque, Lafraire, & Auvray, 2020). Taking this research forward, the current paper adds further evidence of the effect of brand names and consonants on carbonation perception.…”
Section: Spiky Sounds Sparklingmentioning
confidence: 99%